Conflicting claims in the eurozone? Austerity's myopic logic and the need for a European federal union in a Post-Keynesian eurozone center-periphery model - Alberto Botta (Levy Economics Institute of Bard College, 2012)
In this paper, we analyze the role of the current institutional setup of the eurozone in fostering the ongoing peripheral euro countries' sovereign debt crisis. In line with Modern Money Theory, we stress that the lack of a federal European government running anticyclical fiscal policy, the loss of euro member-states' monetary sovereignty, and the lack of a lender-of-last-resort central bank have significantly contributed to the generation, amplification, and protraction of the present crisis. In particular, we present a Post-Keynesian eurozone center-periphery model through which we show how, due to the incomplete nature of eurozone institutions with respect to a full-fledged federal union, diverging trends and conflicting claims have emerged between central and peripheral euro countries in the aftermath of the 2007-08 financial meltdown. We emphasize two points. (1) Diverging trends and conflicting claims among euro countries may represent decisive obstacles to the reform of the eurozone toward a complete federal entity. However, they may prove to be self-defeating in the long run should financial turbulences seriously deepen in large peripheral countries. (2) Austerity packages alone do not address the core problems of the eurozone. These packages would make sense only if they were included in a much wider reform agenda whose final purpose was the creation of a government banker and a federal European government that could run expansionary fiscal stances. In this sense, the unlimited bond-buying program recently launched by the European Central Bank is interpreted as a positive, albeit mild step in the right direction out of the extreme monetarism that has thus far shaped eurozone institutions.
Keywords: E02; E12; H63; 330; eurozone debt crisis; Modern Money Theory; Post-Keynesian center-periphery model